2015
DOI: 10.3945/ajcn.114.097394
|View full text |Cite
|
Sign up to set email alerts
|

Is achlorhydria a cause of iron deficiency anemia?

Abstract: We re-evaluated the old hypothesis that gastritis-induced achlorhydria is a cause of iron deficiency anemia (IDA) in humans. First, we analyzed the currently available research on the association between achlorhydria and IDA. When gastric acid secretion was measured after maximal stimulation, the frequency of achlorhydria (or severe hypochlorhydria) was 44% in patients with idiopathic IDA and 1.8% in healthy controls. In some patients with pernicious anemia, presumed achlorhydria preceded the development of ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 76 publications
0
21
0
1
Order By: Relevance
“…9 Gastric juice ascorbic acid and low gastric pH are important factors in the absorption of dietary iron. 76,77 showed more frequent atrophic gastritis in patients with unexplained IDA than in their matched controls; the former also displayed more frequent corpus gastritis, while similar proportions of antrum gastritis were found in both groups. 79 Kaye et al 27 showed that among patients who underwent investigation for anemia, body atrophy was sevenfold more prevalent than among controls; and a positive dose-response association was found between gastric body atrophy and anemia.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…9 Gastric juice ascorbic acid and low gastric pH are important factors in the absorption of dietary iron. 76,77 showed more frequent atrophic gastritis in patients with unexplained IDA than in their matched controls; the former also displayed more frequent corpus gastritis, while similar proportions of antrum gastritis were found in both groups. 79 Kaye et al 27 showed that among patients who underwent investigation for anemia, body atrophy was sevenfold more prevalent than among controls; and a positive dose-response association was found between gastric body atrophy and anemia.…”
Section: Discussionmentioning
confidence: 78%
“…The level of gastric juice ascorbic acid was found to be significantly lower in individuals infected with CagA‐positive strains than in those with CagA‐negative strains . Gastric juice ascorbic acid and low gastric pH are important factors in the absorption of dietary iron . Thus, H. pylori ‐induced alteration in gastric pH levels and/or gastric juice ascorbic acid levels may be expected to affect the homeostasis of iron biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The stomach is an active reservoir that stores, triturates, and slowly dispenses partially digested food into the intestine for further digestion and absorption, and also controls appetite and satiety . Its main secretory function is secretion of gastric acid, which initiates peptic hydrolysis of dietary proteins, liberates vitamin B12 from dietary protein, facilitates duodenal absorption of inorganic iron and calcium, stimulates pancreatic HCO 3 − secretion via secretin release, suppresses antral gastrin release, and modulates the intestinal microbiome by killing microorganisms and preventing bacterial overgrowth . Comprehensive overviews of the regulation of gastric acid secretion (Supplement 1) and regulation of gastric mucosal barrier function (Supplement 2) are available in the Supporting Information.…”
Section: Physiologic Role Of Gastric Acidmentioning
confidence: 99%
“…AIG, first described by Faber in 1909 as achlorhydric gastric atrophy , is a chronic progressive inflammatory condition leading to the decrease or disappearance of parietal cells, which results in reduced or absent acid production (hypochlorhydria or achlorhydria)[ 59 ].The lack of gastric acidity has only recently been confirmed as key factor for impaired intestinal iron absorption[ 60 ]. IDA is more often associated with AIG than classical pernicious anemia and frequently precedes vitamin B 12 deficiency (at least in fertile women)[ 61 , 62 ].…”
Section: Anemia and Id In Different Conditionsmentioning
confidence: 99%